2019
DOI: 10.1246/bcsj.20190094
|View full text |Cite
|
Sign up to set email alerts
|

Two-Way Chromic Systems Based on Tetraarylanthraquinodimethanes: Electrochromism in Solution and Mechanofluorochromism in a Solid State

Abstract: Tetraarylanthraquinodimethane derivatives 1 with butterfly-shaped folded structures and the corresponding dications 12+ with twisted conformations can undergo interconversion upon two-electron transfer, which is accompanied by a drastic color change. While reversible electrochromic behavior occurs in solution, electron donors 1 exhibit fluorescence only in the solid state. The emission color changed upon grinding as-synthesized samples of 1, and the original emission color was recovered by a dissolving-drying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…Thus, upon electrochemical oxidation of dienes with pyrrolidino ( 3 b ) and morpholino ( 3 c ) groups, electrochromism with drastic change of NIR absorption was demonstrated in each case with an isosbestic point (Figures and S3). Due to the similarity of the absorption in 3 b 2+ and 3 c 2+ , chromic behavior is nearly identical although there is a big difference between their redox potential (Δ E =0.25 V), as in the electrochromism of tetraarylanthraquinodimethanes …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, upon electrochemical oxidation of dienes with pyrrolidino ( 3 b ) and morpholino ( 3 c ) groups, electrochromism with drastic change of NIR absorption was demonstrated in each case with an isosbestic point (Figures and S3). Due to the similarity of the absorption in 3 b 2+ and 3 c 2+ , chromic behavior is nearly identical although there is a big difference between their redox potential (Δ E =0.25 V), as in the electrochromism of tetraarylanthraquinodimethanes …”
Section: Resultsmentioning
confidence: 99%
“…Due to the similarity of the absorption in 3 b 2 + and 3 c 2 + , chromic behavior is nearly identical although there is a big difference between their redox potential (ΔE = 0.25 V), as in the electrochromism of tetraarylanthraquinodimethanes. [22] On the contrary, the haloaryl units at 2,3-positions affect the NIR absorption band as shown by the comparison of 1 a 2 + , 2 a 2 + and 3 a 2 + (Figure 2b and Table 3). Thus, attachment of halogen atoms induces red shift of the NIR absorptions, so that the value of λ max becomes greater in the order of 1 a 2 + (681 nm) < 3 a 2 + (751 nm) < 2a 2 + (768 nm).…”
Section: Formation Of Dication Salts and Electrochromic Behaviormentioning
confidence: 93%
See 1 more Smart Citation
“…Although the F form of 11,11,12,12‐tetraarylanthraquinodimethanes IV is far more stable than the corresponding twisted structures (see Table S1 in the Supporting Information), we recently found that the T form is more favored for tetraazaanthraquinodimethane derivatives V , in which all inner C−H groups at the fjord region on the AQD core of IV are replaced with nitrogen atoms. Thus, slight modification of the molecular structure of IV would reduce the Δ E value between the F and twisted structures, and the marginal decrease in steric repulsion around C=C double bonds may favor twisted structures (both T and D forms).…”
Section: Figurementioning
confidence: 96%
“…Normal alkenes have a planar geometry, whereas OCEs are forced to adopt a folded ( F ) and/or twisted ( T ) form, the latter of which, in general, has a higher HOMO and a lower LUMO than the former. Owing to the large difference in the electronic structure (e.g., the T form has a smaller HOMO–LUMO gap), their dynamic structural change is accompanied by a change in physical properties, and thus many studies on OCEs have been devoted to developing chromic materials and molecular switches . As exemplified by bianthrones I and bisthiaxanthylidenes II , which are classified as bistricyclic aromatic enes (BAEs; Figure a), in many cases the F form is more stable than the corresponding T form by about 5–20 kcal mol −1 .…”
Section: Figurementioning
confidence: 99%